Technology management has a significant impact on digital transformation in the banking sector - Rodrigues, L. F.; Oliveira, A.; Rodrigues, H. (International Review of Economics and Finance, 2023)
Technology management and a good relationship among employees are vital keys to assure any digital transformation process. We may therefore rightly ask “What are the main drivers influencing IT and non-IT employee relationships that may have an impact on digital transformation in the banking sector?“. Aiming to identify those drivers, we developed a questionnaire for an exploratory study into employees' perceptions of the IT or non-IT measures undertaken to improve any digital transformation project. We had a sample of 604 bank employees working in software development. Leximancer was used as a qualitative technique tool for content textual analyses. The findings highlighted seven key factors that have an impact on digital transformation, namely: department, lack of cooperation, communication, requests, experience, relationship, and business. Internal clients tend to have a negative perception of IT developers mainly due to a lack of understanding of business requests. This study contributes to scholarship with a conceptual model to explain the main concepts that may affect the relationship between IT and non-IT employees’ and departments teamwork in the digital transformation process, in the banking sector specifically. We also contribute by identifying the most important elements to achieve organizational success.